Republic of Moldova : Financial Sector Assessment Program-Detailed Assessment of Observance on the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2016)
The National Bank of Moldova (NBM) has made significant progress in reinforcing its prudential and supervisory framework. Two medium-term strategies have been designed in succession since 2008 to set a forward-looking approach for supervision. The most recent one spanning four years (2013-17) aims to ensure a higher level of efficiency, transparency, and performance of the NBM by bringing the best international practices, particularly, in the area of corporate governance. The country is also in the process of transitioning from Basel I to Basel II. In the context of an Association Agreement to be signed with the European Union (EU),2 the NBM plans to implement the standard risk-weighting model of Basel II as well as other elements of Basel III. The objective is to enhance the NBM's institutional capacity with the view to foster the banks' prudential regulatory framework. The association process will also enable NBM to gradually implement the EU Capital Requirements Regulation and Directive (CRR/CRD).